Does Structural Violence by Institutions Enable Revictimization and Lead to Poorer Health Outcomes?-A Public Health Viewpoint - Gloria Macassa (Ubiquity Press, 2023)
Although structural violence is known to interact with and reinforce direct violence in the form of interpersonal violence (e.g., intimate partner violence), little debate takes place in public health on how it can lead to revictimization, leading to even poorer health outcomes (including psychological ill health). This viewpoint aims to discuss this issue using examples from empirical studies to elucidate how structural violence (perpetrated through institutions) contributes to revictimization among people who are already suffering direct violence. Public health professionals (and researchers) need to make efforts to theorize and measure structural violence to aid efforts toward the study of how it intersects with interpersonal violence to influence health outcomes. This will ultimately contribute to better prevention and intervention efforts to curb interpersonal violence and improve population health and well-being. In addition, there is a need to include structural violence in the academic curriculum when training future generations of public health professionals. Increased education on structural violence will bring about an awareness of the grave consequences of the potential additional harm that institutions could inflict on the lives of people they should be protecting or care for.